Effects of Refiring Processes on Electrical and Structural Properties of Thick-Film Resistors. (1980) - Cattaneo, A.; Prudenziati, M.
Abstract : in order to analyze the influence of the refiring processes in thick film resistors, electrical and structural properties of resistors, refired up to ten times, through the original profile, were compared. The apparent sheet resistivity and TCR were measured as a function of the number of the firing cycles, and these electrical characteristics analyzed in connection with observations of structural and chemical modifications evidenced through X-ray diffraction, SEM inspection and microprobe analysis. Marked effects were observed, such as segregation of the conductive grains in the resistor thickness, chemical reactions of glass-modifiers with glass, crystallization of new phases, together with substrate/thick-film interactions. It is found that in some cases (e.g. for DP 1400 resistor series) the phenomena induced by refiring are few and simple enough for us to interprete the corresponding electrical modifications, while in other systems the presence of many competitive chemicophysical effects inhibit their unambiguous correlation with the electrical properties of these resistors.